Biodiversity Information System for Management of Medicinal Plants Data Tropical Rainforest Borneo - Angelina Widians, Joan; Wati, Masna; Tejawati, Andi; Budiman, Edy (International Journal of Engineering and Technology, 2018)
This paper is an effort to inform about the potential of medicinal plants in forest areas in the Borneo region. Given the high rate of destruction of rainforests on Borneo, literacy and conservation efforts of medicinal plants that are part of the forest ecosystem are important. This study developed BBIS, namely Borneo Biodiversity Information System. BBIS is the development of computer-based technology for managing information on Borneo's natural resource biodiversity in order to improve the knowledge management of medicinal plants. In particular, development of the Biodiversity Information System which can be used as an exploring media for exchange information society on Borneo's biodiversity. Profile biodiversity complete and well managed will be a reference in the process of monitoring the use of biological diversity, strategies, and plans related to the biodiversity of the medicinal plants on Borneo Island.Â Â